2019
DOI: 10.1177/1077801219882505
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Persuasion: Young Fijian Women’s Experiences of Sexual and Reproductive Coercion in Romantic Relationships

Abstract: Intimate partner violence (IPV) is a violation of women’s human rights and dramatically increases women’s vulnerability to sexual and reproductive health morbidities. This article examines young iTaukei (Indigenous Fijian) women’s experiences of, and responses to, nonphysical forms of coercion in romantic relationships. It draws on ethnographic research with young unmarried women attending university in Suva, Fiji. Young women disclosed experiencing a continuum of coercive behaviors, including verbal pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Data were collected between June 2011 and September 2012 in Suva, Fiji. This paper, which is one of several describing findings from the study, 11,25,26 explores the contextual influences on young people's condom use practices in premarital relationships.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected between June 2011 and September 2012 in Suva, Fiji. This paper, which is one of several describing findings from the study, 11,25,26 explores the contextual influences on young people's condom use practices in premarital relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Young women reported that male partners frequently determined whether condoms could be used, and used a range of tactics to coerce women into having sex without a condom, including verbal pressure, subtle manipulation and deception. 11,26 'Even with words there is so much pressure . .…”
Section: Barriers To Condom Usementioning
confidence: 99%
“…All studies included the perspectives of women, four studies were mixed methods and 29 were qualitative studies. Of the 33 studies, 16 were from USA [ 3 , 29 43 ], four from Kenya [ 44 47 ], three from Australia [ 48 – 50 ], two from India [ 51 , 52 ], and one each from Brazil [ 53 ], Fiji [ 54 ], Iran [ 55 ], England [ 56 ], Sweden [ 57 ], Mexico [ 58 ], Ecuador [ 59 ] and Canada [ 5 ]. Nine studies specifically explored experiences of low-income women [ 30 , 33 , 36 , 37 , 40 , 41 , 43 , 51 , 52 ].…”
Section: | Resultsmentioning
confidence: 99%
“…Reproductive coercion and abuse was the primary phenomena of interest in 13 studies [ 3 , 5 , 29 , 40 42 , 44 , 47 , 48 , 50 , 54 , 58 ]. Reproductive coercion and abuse was a secondary phenomena of interest in the other studies, which focused on women’s experiences with intimate partner violence (IPV) particularly sexual violence [ 31 , 53 , 57 ], the effects of abuse or IPV on women’s reproduction [ 32 35 , 39 , 43 , 45 , 46 , 51 , 55 , 56 ], factors affecting women’s pregnancy intentions [ 30 , 36 , 49 , 52 ], barriers to contraception use [ 37 ] and son preferences [ 38 ].…”
Section: | Resultsmentioning
confidence: 99%
See 1 more Smart Citation